OpEd: Republicans play dirty because Republican policies are unpopular - Monica Prasad (economic sociology_the european electronic newsletter, 2020)
For some years now Republicans at state and national level have been playing what some scholars have called 'constitutional hardball,' implementing strategies that, while technically legal, undermine the spirit of the laws: stealing a Supreme Court seat, tricking Democrats into being absent for crucial votes, suppressing votes. Harvard scholars Steven Levitsky and Daniel Ziblatt (2019) suggest that this is because the Republican Party's base of white voters is shrinking, and Republicans would lose in a fair electoral contest. The long-term solution, they argue, is for the party to diversify.
Keywords: 300